Wind turbines : - Hau, Erich (Springer, 2013)
Wind Turbines addresses all those professionally involved in research, development, manufacture and operation of wind turbines. It provides a cross-disciplinary overview of modern wind turbine technology and an orientation in the associated technical, economic and environmental fields. In its revised third edition, special emphasis has been given to the latest trends in wind turbine technology and design, such as gearless drive train concepts, as well as on new fields of application, in particular the offshore utilisation of wind energy. The author has gained experience over decades designing wind energy converters with a major industrial manufacturer and, more recently, in technical consulting and in the planning of large wind park installations, with special attention to economics.